A platform for designing quantitative infrared spectrophotometric method for drugs and pharmaceuticals analysis: a rediscover for an ecological and safer technique in the routine quality control laboratories - Corrêa, Josilene Chaves Ruela [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2014)
This paper describes the importance of an innovative analytical technique for drugs and pharmaceuticals quantification, using Fouriertransform infrared (FTIR) transmission spectroscopy. This method does not use organic solvents, which is one great advantage over the most common analytical methods. This fact contributes to minimize the generation of organic solvent waste by the industry and thereby reduces the impact of its activities on the environment. The method involved absorbance measurements of the band corresponding to one of the chosen group in the molecule. Obviously, the method should be validated according to ICH guidelines, showing linearity, precision, accuracy and robustness, over a concentration range, using small amounts to prepare the analyte. The validated method is able to quantify drugs and pharmaceuticals and can be used as an environmentally friendly alternative for the routine analysis in pharmaceutical industry quality control.
Keywords: Analytical Methods; FTIR; Green Pharmacy; Quality Control; Spectroscopy; Quantitative; Validation